Principles and methods to guide education for purpose: a Brazilian experience. Issue 5 (19th October 2016) - Araujo, Ulisses F.; Arantes, Valeria Amorim; Danza, Hanna Cebel; Pinheiro, Viviane Potenza Guimarães; Garbin, Monica
Abstract: This article presents a Brazilian experience in training teachers to educate for purpose. Understanding that purpose is a value to be constructed through real-world and contextualised experiences, the authors discuss some psychological processes that underlie purpose development. Then the authors show how these processes are used in a purpose development programme they have conducted for in-service and pre-service teachers over the past six years. Using innovative pedagogies, such as Problem-Based Learning, Project-Based Learning, and Design Thinking, the authors describe the steps that teachers have to follow in project development, examples of the results accomplished with this kind of programme, and research findings that are being conducted to analyse the principles and results of this approach for training teachers in how to educate youth for purpose.